The impact of heir property on post-Katrina housing recovery in New Orleans - Kluckow, Richard, author; Peek, Lori, advisor; Hempel, Lynn, committee member; Trumbo, Craig, committee member (Colorado State University. Libraries, 2014)
This thesis examines the impact of heir property on post-Katrina housing recovery in New Orleans. Heir property is a form of collective ownership of immoveable property that is the result of intestate succession prevalent in poor and minority communities. For decades, vulnerabilities associated with heir property have been a leading cause of land loss for rural African Americans. After Hurricane Katrina, urban heir property owners in New Orleans struggled to collect insurance money or access federal recovery grants due to issues of unclear title. This research draws on 15 in-depth interviews with institutional actors working on heir property issues in New Orleans and heir property owners in and around the Lower Ninth Ward, a neighborhood devastated by flooding and with high levels of heir property. Specific mechanisms that contributed to lower levels of recovery for heir property owners are identified and recommendations made to protect this particularly vulnerable group of homeowners in future housing recovery programs.
Keywords: disaster; heir property; housing; land tenure; recovery; vulnerability